Abracadabra Games Guna Meningkatkan Kemampuan Berfikir Kritis Anak - Aprila Wanda Paradita; Fajar Nugraha (UIN Sultan Maulana Hasanudin Banten, 2023)
This article discusses research related to the application of the scientific experimental method as an effort to improve the critical thinking skills of early childhood (5-6 years). This study aims to observe the initial conditions of early childhood critical thinking skills before being given treatment or implementing learning activities using the scientific experimental method. This research was conducted in Group B (5-6 years) SPS TAAM Nurul Cendekia Cibeureum Tasikmalaya City. There were 17 research subjects, consisting of 10 girls and 7 boys. This type of research uses Classroom Action Research (PTK) which is carried out in 3 cycles. The instrument used is an observation sheet for early childhood critical thinking skills. The results of the 3-cycle study showed that there was an increase in the critical thinking skills of early childhood through science experiment activities. The results of children's learning with the scientific experimental method managed to achieve a higher percentage than before. a capability that is characterized by four aspects of creativity: fluency, flexibility, originality, and elaboration.